2016
DOI: 10.1371/journal.pone.0154366
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Role of IFITM Proteins in African Swine Fever Virus Infection

Abstract: The interferon-induced transmembrane (IFITM) protein family is a group of antiviral restriction factors that impair flexibility and inhibit membrane fusion at the plasma or the endosomal membrane, restricting viral progression at entry. While IFITMs are widely known to inhibit several single-stranded RNA viruses, there are limited reports available regarding their effect in double-stranded DNA viruses. In this work, we have analyzed a possible antiviral function of IFITMs against a double stranded DNA virus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 38 publications
4
59
0
Order By: Relevance
“…Esparza, Gonzalez, and Vinuela () reported that pre‐treatment of porcine macrophages with IFN‐α significantly inhibited ASFV replication. Additionally, Muñoz‐Moreno et al () have recently shown that pre‐treatment of Vero cells with IFN abrogates ASFV infection and induces interferon‐induced transmembrane (IFITM) protein expression, suggesting that IFITM could be involved in natural antiviral mechanisms to ASFV. ASFV encodes diverse and unique proteins that interfere with and down‐regulate the expression of many host immunomodulatory proteins (Correia et al, ; Dixon et al, ; Miskin, Charles, Lynnette, & Dixon, ; Sánchez, Quintas, Nogal, Castelló, & Revilla, ).…”
Section: The Quest Of Immune Evasion Mechanisms Could Guide Asf Vaccimentioning
confidence: 99%
“…Esparza, Gonzalez, and Vinuela () reported that pre‐treatment of porcine macrophages with IFN‐α significantly inhibited ASFV replication. Additionally, Muñoz‐Moreno et al () have recently shown that pre‐treatment of Vero cells with IFN abrogates ASFV infection and induces interferon‐induced transmembrane (IFITM) protein expression, suggesting that IFITM could be involved in natural antiviral mechanisms to ASFV. ASFV encodes diverse and unique proteins that interfere with and down‐regulate the expression of many host immunomodulatory proteins (Correia et al, ; Dixon et al, ; Miskin, Charles, Lynnette, & Dixon, ; Sánchez, Quintas, Nogal, Castelló, & Revilla, ).…”
Section: The Quest Of Immune Evasion Mechanisms Could Guide Asf Vaccimentioning
confidence: 99%
“…Peptides were separated using a 90 min linear gradient (from 1% acetonitrile, 0.1% formic acid to 40% acetonitrile, 0.1% formic acid) and on-line electrosprayed into an LTQ Orbitrap XL mass spectrometer equipped with a nanospray ion source (both Thermo). The mass spectrometer operated in data dependent acquisition (DDA) mode, controlled by the software Xcalibur (version 2.0.7, Thermo) to acquire both full MS spectra in the m/z range 320-1400 (resolution 1 × 10 5 FWHM at m/z 400) and MS/MS spectra obtained by collision induced dissociation [30][31][32][33][34][35][36] (CID) of the 6 most abundant multi-charged ions. Automatic gain control (AUG) was set at 1 × 10 6 for the acquisition of full MS spectra and at 1 × 10 5 for MS/MS spectra.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%
“…CH25H catalyzes 25hydroxycholesterol production to inhibit PRV entry. In addition, IFN-inducible transmembrane proteins (IFITMs) are a group of antiviral restriction factors that act against a broad range of viruses [13], such as influenza A virus [14], human immunodeficiency virus (HIV)-1 [15], West Nile virus and dengue virus [16], vesicular stomatitis virus [17], severe acute respiratory syndrome coronavirus and Marburg virus [18], classical swine fever virus [19] and African swine fever virus [20]. The mechanisms by which IFITMs influence virus infection are restriction of viral entry, viral assembly or viral protein synthesis [21].…”
Section: Introductionmentioning
confidence: 99%